Performance and Absolute Music Composition Design Based on Experimentation of Sundanese Flute - Arita Bagja Pramudita; Budi Garda Pandawa; Dwi Yulisa; Febrika Cahyadi Sammbodo; Gerardus P Korohama (Pascasarjana ISBI Bandung Conference Series, 2025)
The act of breathing symbolizes human life and the preservation of its existence. Music, serving as a symbol of auditory influence in human life, also exerts an impact and persuasion on individuals, contributing to the construction of their character. The portrayal of human life and auditory influence serves as the foundation for the creation of an absolute musical composition show, grounded in the experimentation of breath patterns on the Sundanese flute. The method of creation adopts experimental theory to compose absolute music devoid of predetermined aesthetic perspectives. This method is also directed towards the creation of therapeutic music, aiming to provide a contemplative terminal deposit for its listeners. Keywords: Absolute music, experimentation, breath, flute, audio spatial